The land-sea breeze influences the oceanography of the southern Benguela upwelling system at multiple time-scales - Fearon, Giles; Herbette, Steven; Cambon, Gildas; Veitch, Jennifer; Meynecke, Jan-Olaf; Vichi, Marcello (Frontiers in Marine Science, 2023)
The physical and biogeochemical functioning of eastern boundary upwelling systems is generally understood within the context of the upwelling - relaxation cycle, driven by sub-diurnal wind variability (i.e. with a time-scale of greater than a day). Here, we employ a realistically configured and validated 3D model of the southern Benguela upwelling system to quantify the impact of super-diurnal winds associated with the land-sea breeze (LSB). The ocean response to the LSB is found to be particularly enhanced within St Helena Bay (SHB), a hotspot for productivity which is also prone to Harmful Algal Bloom (HAB) development. We attribute the enhanced response to a combination of near-critical latitude for diurnal-inertial resonance (~32.5°S), the local enhancement of the LSB, and the local development of a shallow stratified surface layer through bay retention. Pronounced advection of the surface layer by diurnal-inertial oscillations contributes to large differences in day- and night-time sea surface temperatures (SST’s) (more than 2°C on average in SHB). Event-scale diapycnal mixing is particularly enhanced within SHB, as highlighted by a numerical experiment initialised with a subsurface passive tracer. These super-diurnal processes are shown to influence sub-diurnal dynamics within SHB through their modulation of the vertical water column structure. A deeper thermocline retains the upwelling front closer to land during active upwelling, while geostrophically-driven alongshore flow is impacted through the modulation of cross-shore pressure gradients. The results suggest that the LSB is likely to play an important role in the productivity and therefore HAB development within SHB, and highlight potential challenges for observational systems and models aiming to improve our understanding of the physical and biological functioning of the system.